(untitled) (Journal of Hama University, 2019)
This research was performed to study the histological changes caused by Mycoplasma gallisepticum (MG) in lung tissues of broiler chicken. Ten live birds of forty day old were collected. Bird showed symptoms of Mycoplasma infection. Blood samples were obtained and tested by ELIZA test to confirm the infection. These birds were slaughtered and autopsied. Lung tissues were collected in 10% buffered formalin. Infected birds suffered from runny nose and eyes, swelling around the eyes and conjunctivitis. The ELISA test of blood samples were positive in 80% of birds. Grossly, lung tissues of affected birds were hyperemic with different intensity. lungs were consolidated and covered with fibrin layer. Histologically, there was hyperplasia in the Mucous layer of primary bronchioles, absence of cilia. Degeneration and necrosis of mucous glands were observed. Secondary and tertiary bronchioles were inflamed and infiltrated with macrophages, lymphocytes, heterophils and fibroblastsis.